Vertical stratification and air-sea CO2 fluxes in the Patagonian shelf - Bianchi, A.A. (2005)
The thermohaline structure across the tidal fronts of the continental shelf off Patagonia is analyzed using historical and recent summer hydrographic sections. The near-summer tidal front location is determined on the basis of the magnitude of vertical stratification of the water column as measured by the Simpson parameter. Sea surface and air CO2 partial pressures based on data from eleven transects collected in summer and fall from 2000 to 2004 are used to estimate CO2 fluxes over the shelf. The near-shore waters are a source of CO2 to the atmosphere while the midshelf region is a CO2 sink. The transition between source and sink regions closely follows the location of tidal fronts, suggesting a link between vertical stratification of the water column and the regional CO2 balance. The highest surface values of Chl a are associated with the strongest CO2 sinks. The colocation of lowest CO2 partial pressure (pCO2) and highest Chl a suggests that phytoplankton blooms on the stratified side of the fronts draw the ocean's CO2 to very low levels. The mean shelf sea-air difference in pCO2 (ΔpCO2) is -24 μatm and rises to -29 μatm if the shelf break front is included. Peaks in ΔpCO2 of -110 μatm, among the highest observed in the global ocean, are observed. The estimated summer mean CO2 flux over the shelf is -4.4 mmol m-2 d-1 and rises to -5.7 mmol m-2 d-1 when the shelf break area is taken into account. Thus, during the warm season the shelf off Patagonia is a significant atmospheric CO2 sink. Copyright 2005 by the American Geophysical Union.